MPPT Circuit Using Time Exponential Rate Perturbation and Observation for Enhanced Tracking Efficiency for a Wide Resistance Range of Thermoelectric Generator - Jie Miao; Houpeng Chen; Yu Lei; Yi Lv; Weili Liu; Zhitang Song (Applied Sciences, 2021)
The thermoelectric generator (TEG) stands out among many energy harvesters due to its simple structure, small size, rich thermal energy, and the absence of pollution and noise. However, previous studies have rarely probed into the influence of TEG internal resistances on extracting maximum power from TEGs, and the tracking of efficiency is limited. By analyzing the relationship between the tracking efficiency and the TEG internal resistances, a time exponential rate perturbation and observation (P&O) technology is proposed to achieve maximum power point tracking (MPPT) for a wide resistance range of the TEG. Using the time exponential rate P&O, the MPPT circuit observed the power change by comparing the positive-channel metal-oxide semiconductor (PMOS) on-time and perturbs the power by adjusting the negative-channel metal-oxide semiconductor (NMOS) on-time exponentially. The MPPT circuit was implemented in a 110 nm complementary metal-oxide semiconductor (CMOS) process. The tracking efficiency maintained a high level from 98.9 to 99.5%. The applicable range of the TEG resistance was from 1 to 12 Ω, which reflects an enhancement of at least 2.2 times.